Cancer mortality in an international cohort of reinforced plastics workers exposed to styrene: a reanalysis. Issue 3 (17th April 2018) - Loomis, Dana; Guha, Neela; Kogevinas, Manolis; Fontana, Vincenzo; Gennaro, Valerio; Kolstad, Henrik A; McElvenny, Damien Martin; Sallmén, Markku; Saracci, Rodolfo
Abstract : Objective: To investigate the carcinogenicity of styrene by reanalysing data from a previous international cohort study of workers in the reinforced plastics industry. Methods: Mortality from cancers of prior interest was analysed with more detailed consideration of exposure–response relations and an updated classification of leukaemias and lymphomas in data from a previous international cohort study of 37 021 reinforced plastics workers exposed to airborne styrene. Results: Increased mortality from non-Hodgkin's lymphoma (NHL) was associated with the mean level of exposure to styrene in air (relative risk (RR) 2.31, 95% CI 1.29 to 4.12 per 100 ppm), but not with cumulative styrene exposure. Similar associations with mean exposure were observed for the oesophagus (RR 2.44, 95% CI 1.11 to 5.36 per 100 ppm) and pancreas (RR 1.89, 95% CI 1.17 to 3.09). Oesophageal cancer mortality was also associated with cumulative styrene exposure lagged 20 years (RR 1.16, 95% CI 1.03 to 1.31). No other cancer, including lung cancer, was associated with any indicator of styrene exposure. Conclusion: This reanalysis does not substantially change the conclusions of the original study with respect to NHL or lung cancer but new evidence concerning cancers of the oesophagus and pancreas merits further investigation.